Study of Road Environmental Capacity in the School Area in Banda Aceh City - Fadhly, Noer; Zaki, Muhammad (Talenta Publisher, 2025)
The study discusses the relationship between the environmental capacity of the road in terms of the impact of noise and air pollution caused by vehicles traveling on the road around the school area, namely T. Panglima Nyak Makam in Banda Aceh. Level of noise and air pollution is greatly influenced by the geometric of the road, the volume and, the speed of the vehicle. Traffic volume average of 486.8 pcu/hour/direction and an average speed of 33.19 km/hour. Capacity of this road is 1455.3 pcu/hour. From the research results obtained Leq values ​​ranged from 72.8 dB (A) - 78.2 dB (A), with an average value of 76.00 dB (A). This Leq value indicates a noise level that has an impact on the community that is greater than 70 dB (A), and is still within the maximum noise threshold of 85 dB (A) and has passed the noise standard in the school area of ​​55 dB (A), then This road section is no longer feasible for school areas if assessed from the noise that occurs, for CO pollutants (LV) 1,301 ppm, CO (HV) 0.016 ppm, NOX 0.096 ppm, and HC 0.063 ppm. This shows that is still feasible because the DS limit for urban roads is 0.85 and classified as this road is still able to accommodate the traffic volume with the estimated air pollution provided.